Phytochemical analysis and antidiabetic, antibacterial, and antifungal activities of leaves of Bursera simaruba (Burseraceae) - Infante-Rodríguez, Dennis Adrián; Landa-Cansigno, Cristina; Gutiérrez-Sánchez, Angélica; Murrieta-León, Diana Lizzet; Reyes-López, Celeste; Castillejos-Pérez, Adriana Belén; Pucheta-Fiscal, José Efrain; Velázquez-Narváez, Alberto Carlos; Monribot-Villanueva, Juan Luis; Guerrero-Analco, José Antonio (Instituto de Ecología, A.C., 2022)
Background and Aims: Bursera simaruba leaves are traditionally used to treat various illnesses. Nonetheless, there are few reports on the description of the phytochemicals potentially responsible for such biological activities. Therefore, this study aimed to describe the antifungal, antibacterial, and antidiabetic potential by using in vitro experiments, and to contribute to the knowledge of the chemical composition of B. simaruba leaves. Methods: A methanolic extract (MeOH-Ex) of B. simaruba leaves was tested for antibacterial, antifungal, and antidiabetic activities, and different groups of secondary metabolites were detected by qualitative assays. Furthermore, phytochemical analysis of MeOH-Ex was carried out by ultra-high performance liquid chromatography coupled to high-resolution mass spectrometry (UHPLC-ESI+-MS-QTOF), and putative identifications were performed using public spectral databases. Key results: The MeOH-Ex of the leaves of B. simaruba qualitatively contains alkaloids, terpenes and steroids, saponins, tannins, coumarins and phenolic compounds, such as caffeic acid, chlorogenic acid, apigenin, kaempferol, phlorizin, quercitrin, quercetin-glucoside and apigenin-glycoside. In addition, burseran and yatein lignans were tentatively identified. MeOH-Ex exhibited low antifungal activity against Fusarium solani (16.3% mycelial growth inhibition) and a high antidiabetic effect by in vitro inhibition of α-amylase (87.7%) and α-glucosidase (75.9%) enzymes. Finally, chlorogenic acid standard exhibited a significant inhibition of α-amylase (49.5%) and α-glucosidase (85.1%) enzymes. Conclusions: The MeOH-Ex of B. simaruba leaves represents a source of secondary metabolites with potential antidiabetic activity. The phenolic compounds tentatively identified could play important roles in preventing disorders due to post-prandial hyperglycemia by inhibiting the enzymes α-amylase and α-glucosidase. Chlorogenic acid presence is highlighted as one of the main potential bioactive compounds in B. simaruba leaves.